Efektivitas Ekstrak Serai Dapur (Cymbopogon citratus DC.) untuk Pengendalian Hama Gudang (Sitophilus oryzae L.) pada Beras (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Rice is the main food that affects the welfare of the Indonesian people. Rice storage is one of the important stages, because during this period it is undergoing a process of decreasing quality and quantity. The test was arranged using a completely randomized design (CRD) with 6 treatments and 4 replications, this experiment was carried out using concentrations of: P1 = 5%; P2 = 10% : P3 = 15% ; P4 = 20% ; P5 = 25%; P0 = not given treatment. The results showed that the concentration of lemongrass extract had an effect on the mortality of S. oryzae in rice. Lemongrass extract concentration 25% can cause 61.50% mortality, 20% concentration can cause 37.50% mortality, 15% concentration can cause 25.00% mortality, 10% concentration can cause 17.50% mortality, and 5% concentration can cause 10% mortality. The more concentration of lemongrass extract given, the more active compounds, the greater the effect of insect mortality. Based on the results of research and discussion of 25,00% concentration, it was effective for controlling warehouse pests on S. oryzae rice with a mortality of 61.50%.